Prevalence and associated factors of hypertension among adult patients attending the outpatient department at the primary hospitals of Wolkait tegedie zone, Northwest Ethiopia - Belay, Daniel Gashaneh; Fekadu Wolde, Haileab; Molla, Meseret Derbew; Aragie, Hailu; Adugna, Dagnew Getnet; Melese, Endalkachew Belayneh; Tarekegn, Gebrekidan Ewnetu; Gezahegn, Eleleta; Kibret, Anteneh Ayelign (Frontiers in Neurology, 2022)
Introduction: Hypertension, often known as increased blood pressure, is a worldwide public health concern. Globally about one billion people have hypertension and 7.1 million die from this disease. It is disproportionately more prevalent in resource-poor nations, with inadequate health systems like Ethiopia. Moreover, information on the burden of disease from hypertension in the specific area especially in the newly organized Wolkait tegedie zone is essential to develop effective prevention and control strategies. Therefore, this study aimed to assess the prevalence of hypertension and associated factors among adult patients evaluated at the outpatient department of the two district hospitals Wolkait tegedie zone Northwest Ethiopia. Methods: An institution-based cross-sectional study was conducted from September to October 2021. A systematic random sampling technique was used to select a total of 449 participants. Bivariable and multivariable binary logistic regression analyses were performed. Adjusted odds ratio (AOR) with a 95% confidence interval was used as a measure of association. Variables having P-value < 0.05 from the multivariable analysis were considered to have a significant association with the outcome. Results: The prevalence of hypertension among adult patients in this study was 44.91% [95%CI: 40.26%, 49.65%], of which 63.92% were the newly diagnoses. Being above 60 years [AOR =1.81; 95%CI: 1.11, 3.20], having poor physical exercise [AOR =1.74; 95%CI: 1.01, 3.15], patients who consumed cruddy oil [AOR =15.22; 95%CI: 3.86, 60.12], have a family history of hypertension [AOR =13.02; 95%CI: 3.75, 45.16], and having a history of DM [AOR =8.05; 95%CI: 1.24, 51.49] had a statistical significantly associated with having hypertension. Conclusion: There is a relatively high prevalence of hypertension among adult patients in the outpatient department of the two primary hospitals, in Northwest Ethiopia. Factors such as being older age, having poor physical exercise behavior, cruddy oil consumption, and family history of diabetes mellitus and hypertension had a positive significant statistical association with being hypertensive. Community-based screening programs for hypertension should design and implement to prevent this silent killer disease. Health education and promotion which focuses on healthy nutrition and physical exercise should be delivered.